Influence of the pH control strategy and reactor volume on batch fermentative hydrogen production from the organic fraction of municipal solid waste. Issue 5 (May 2019) - Baldi, Francesco; Iannelli, Renato; Pecorini, Isabella; Polettini, Alessandra; Pomi, Raffaella; Rossi, Andreina
Three different experimental sets of runs involving batch fermentation assays were performed to evaluate the influence of the experimental conditions on biological hydrogen production from the source-separated organic fraction of municipal solid waste collected through a door-to-door system. The fermentation process was operated with and without automatic pH control, at a pH of 5.5 and 6.5, food-to-microorganism ratios of 1/3 and 1/1 (wet weight basis) and with different working volumes (0.5 and 3 L). The experimental results showed that the pH control strategy and the reactor volume did not affect the final hydrogen production yield but played an important role in determining the time evolution of the process. Indeed, although the different experimental conditions tested yielded comparable hydrogen productions (with maximum average values ranging from 68.5 to 88.5 NLH2 (kgTVSOF ) −1 ), the automatic pH control strategy improved the process from the kinetic viewpoint resulting in a t 95 reduction from an average of 34.9 h without automatic pH control to an average of 19.5 h.